Determinan Efektivitas Belanja Daerah dan Dampaknya Pada Pertumbuhan Ekonomi - Natalia Lily; Marsela Wijayanti (Ekopem: Jurnal Ekonomi Pembangunan, 2019)
Increasing local budgets every year should be offset by increasing economic growth, but in fact economic growth has decreased from 2012 to 2015. This study aims to determine the effect of priority, the accuracy of allocation, timeliness, transparency and accountability to the effectiveness of regional expenditure and its impact on economic growth. The sample of this research is all districts and cities in Indonesia. Sources of data used are secondary data from budget reports and realized APBD obtained from the Directorate General of Fiscal Balance Ministry of Finance of the Republic of Indonesia, performance evaluation report of local government implementation (EKPPD) obtained from the Directorate General of Regional Autonomy of the Ministry of Home Affairs of the Republic of Indonesia and data of gross regional domestic product (GRDP) obtained from Indonesian Central Bureau of Statistics. The data used are from 2012 to 2015. Data analysis technique used is Partial Least Square (PLS). The result of the research shows that the priority has influence to the effectiveness of regional expenditure, the accuracy of allocation has no effect on the effectiveness of regional expenditure, the timeliness effect on the effectiveness of regional expenditure, transparency and accountability affect the effectiveness of regional expenditure and effectiveness affect the economic growth.